1, 3-Dipolar cycloaddition of azomethine ylides and imidoyl halides for synthesis of π-extended imidazolium salts. Issue 15 (29th June 2022) - Li, Qiang-Qiang; Hamamoto, Yosuke; Tan, Cheryl Cai Hui; Sato, Hiroyasu; Ito, Shingo
Abstract : A new synthetic approach to π-extended imidazolium salts is developed based on 1, 3-dipolar cycloaddition of polycyclic aromatic azomethine ylides with imidoyl chlorides in the presence of cesium fluoride as a key additive. Abstract : A new synthetic approach to π-extended imidazolium salts is developed based on 1, 3-dipolar cycloaddition of polycyclic aromatic azomethine ylides with imidoyl chlorides, where the key to the successful conversion is the addition of cesium fluoride as an additive. Experimental and theoretical studies revealed that this cycloaddition proceeds via a stepwise mechanism rather than a concerted mechanism. This present method provides an efficient method to synthesize a variety of imidazolium-containing polycyclic aromatic compounds.